Video Teleconferencing in the Compounding Laboratory Component of a Dual-Campus Doctor of Pharmacy Program - Robertson, Jennifer L. (American Journal of Pharmaceutical Education, 2011)
Objectives. To design, implement, and assess the effectiveness of using a live video teleconferencing system to connect the main campus and a satellite campus during laboratory compounding exercises in a doctor of pharmacy (PharmD) program. Design. A new laboratory facility with identical equipment and supplies to the main campus was built at the satellite campus and teleconferencing equipment was set up. Students on both campuses prepared 20 compounded formulations over a 5-course pharmaceutical care laboratory sequence. Live video teleconferencing was used for students to ask questions and for the lead faculty instructor to observe the students’ technique. Faculty and staff members and teaching assistants facilitated the laboratory sessions on both campuses. Assessment. The performance of students on assayed products at the main campus was compared with that of students at the satellite campus to ensure program integrity with the compounding laboratory component. The use of video teleconferencing for teaching compounding was successful and no difference in overall student pass rates was seen. The few observed differences in student performance between the 2 campuses were believed to be a result of variations in instructor communication with distant students. Conclusion. Video teleconferencing can be used successfully to deliver curriculum in laboratory compounding to pharmacy students.